Produksi Perikanan Tangkap di Indonesia: Pendekatan Data Panel pada Aspek Ekonomi, Ekologi, dan Kebijakan - Haris, Rahayu Nurhidayah (Journal of Economics Development Issues, 2025)
Abstract This study aims to analyze the determinants of capture fishery production across 34 Indonesian provinces from 2020 to 2023. Using a panel data regression model, this research examines the influence of economic inputs (number of fishers and vessels), ecological conditions (fish stock status), and policy intervention (the implementation of the Measured Fishing Policy/PIT). The estimation results show that the number of fishers has a positive and statistically significant effect on production volume, confirming the labor-intensive nature of the sector. Conversely, the number of vessels and fish stock status did not show a significant effect within the short observation period. The main finding indicates that the implementation of the PIT policy in 2023 is positively correlated with a 4.4% increase in recorded production volume. This increase is interpreted not as a rise in biological productivity, but as a significant improvement in the accuracy of catch data recording and reporting. Keywords: Blue Economy, Capture Fishery, Measured Fishing Policy Abstrak Penelitian ini bertujuan menganalisis determinan produksi perikanan tangkap di 34 provinsi Indonesia selama periode 2020-2023. Menggunakan model regresi data panel, penelitian ini menguji pengaruh input ekonomi (jumlah nelayan dan kapal), kondisi ekologis (status stok ikan), dan intervensi kebijakan (implementasi Penangkapan Ikan Terukur/PIT). Hasil estimasi menunjukkan bahwa jumlah nelayan memiliki pengaruh positif dan signifikan secara statistik terhadap volume produksi, mengonfirmasi sifat padat karya sektor ini. Sebaliknya, jumlah kapal dan status stok ikan tidak berpengaruh signifikan dalam periode pengamatan. Temuan utama menunjukkan bahwa implementasi kebijakan PIT pada tahun 2023 berkorelasi positif dengan kenaikan volume produksi tercatat sebesar 4,4%. Kenaikan ini diinterpretasikan bukan sebagai peningkatan produktivitas biologis, melainkan sebagai perbaikan signifikan dalam akurasi pencatatan dan pelaporan data hasil tangkapan. Kata kunci: Ekonomi Biru, Penangkapan Ikan Terukur, Perikanan Tangkap